External quality assessment: best practice. Issue 8 (12th March 2014) - James, David; Ames, Darren; Lopez, Berenice; Still, Rachel; Simpson, Wiliam; Twomey, Patrick
Abstract : There is a requirement for accredited laboratories to participate in external quality assessment (EQA) schemes, but there is wide variation in understanding as to what is required by the laboratories and scheme providers in fulfilling this. This is not helped by a diversity of language used in connection with EQA; Proficiency testing (PT), EQA schemes, and EQA programmes, each of which have different meanings and offerings in the context of improving laboratory quality. We examine these differences, and identify what factors are important in supporting quality within a clinical laboratory and what should influence the choice of EQA programme. Equally as important is how EQA samples are handled within the laboratory, and how the information provided by the EQA programme is used. EQA programmes are a key element of a laboratory's quality assurance framework, but laboratories should have an understanding of what their EQA programmes are capable of demonstrating, how they should be used within the laboratory, and how they support quality. EQA providers should be clear as to what type of programme they provide – PT, EQA Scheme or EQA Programme.